(untitled) (Praxis Educativa, 2024)
This research article gives an account of the documentary review on the use of feedback in higher education in Asian countries. The methodology used was PRISMA which allowed selecting articles in databases, such as Scopus, Taylor and Francis, Springerlink and Google Scholar, published in the period 2017-2023. The results of the analysis of 51 documents are presented. The findings were organized into four categories: feedback, types and methods, impact and effectiveness, as well as recent innovations and trends. The results highlight the role of feedback in improving student learning and reveal a diversity of strategies in higher education in Asian contexts.